Estimating the Odds of Ulcerative Colitis-Associated Pyoderma Gangrenosum: A Population-Based Case-Control Study - Kridin, Khalaf; Damiani, Giovanni; Ludwig, Ralf J; Tzur Bitan, Dana; Cohen, Arnon D (Dermatology (Basel), 2021)
Ulcerative colitis (UC) is a well-known underlying comorbidity of pyoderma gangrenosum (PG). However, the risk conferred by UC for the subsequent development of PG is yet to be elucidated. We aimed to estimate the magnitude of the association between UC and the subsequent occurrence of PG, which would enable us to assess the odds of PG developing in individuals with a history of UC. A population-based case-control study was conducted to compare PG patients (n = 302) and age-, sex- and ethnicity-matched control subjects (n = 1,497) regarding the presence of UC. Logistic regression models were utilized for univariate and multivariate analyses. The prevalence of preexisting UC was greater in patients with PG than in controls (7.3 vs. 0.5%; p < 0.001). A 15-fold increase in the odds of PG in individuals with preexisting UC was observed (OR 14.62, 95% CI 6.45-33.18). The greatest risk of developing PG occurred in the first years following the diagnosis of UC (OR 35.50, 95% CI 4.35-289.60), and decreased thereafter to 10.03 (95% CI 1.83-55.03), 6.69 (95% CI 1.49-30.02), and 10.03 (95% CI 1.83-55.03) at 1-5, 5-10, and 10-15 years after the diagnosis of UC, respectively. This association retained its statistical significance following the adjustment for confounding factors (adjusted OR 10.78, 95% CI 4.55-25.52). Patients with both PG and UC were younger and had a lower prevalence of smoking than the remaining patients with PG. UC increases the odds of developing PG by 15-fold, with the highest probability of developing PG occurring within the first year after the diagnosis of UC. Patients with UC may be advised to avoid additional precipitating factors for the development of PG.